1996
DOI: 10.1136/thx.51.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with oral corticosteroids during steroid trials in chronic airways obstruction.

Abstract: Background -Corticosteroid trials are an important part of the assessment of patients with chronic airways obstruction, but false negative results will occur if the treatment is not taken. To determine compliance low dose phenobarbitone has been used as a marker. Methods -Thirty six patients referred to a chest clinic for assessment oftheir airways obstruction were studied. They were instructed to take eight capsules (each containing 5 mg prednisolone and 0-5 mg phenobarbitone) per day for two weeks. The respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…One study using phenobarbitone as a marker of compliance showed that 26% of patients in a corticosteroid trial failed to take the tablets and could have been classified as nonresponsive [3]. In children, several diseases may present with wheezing, including cystic fibrosis and acute viral bronchiolitis.…”
Section: Difficult Asthma Pj Barnes Aj Woolcock Ers Journals Ltmentioning
confidence: 99%
“…One study using phenobarbitone as a marker of compliance showed that 26% of patients in a corticosteroid trial failed to take the tablets and could have been classified as nonresponsive [3]. In children, several diseases may present with wheezing, including cystic fibrosis and acute viral bronchiolitis.…”
Section: Difficult Asthma Pj Barnes Aj Woolcock Ers Journals Ltmentioning
confidence: 99%
“…The consequences may be less severe for some drugs than for others but generally act to reduce the benefits that might be expected from clinical trials 9 10. Patient diaries and tablet counts overestimate the degree of adherence to the prescribed schedule when they are compared with more sophisticated methods of assessment 11 12. We should hardly be surprised that our patients wish to hide their failings from us, and concordance, where the patient and prescriber have discussed in detail the value of adherence, and by implication the price of failure to adhere, may encourage this all too human deceit.…”
mentioning
confidence: 99%
“…Drug efficacy depends not only on biological activity but also on adherence. Studies have shown that, whether administered orally 27 or by inhalation, 28 adherence in subjects with airways disease is less than ideal. Measures to improve adherence, such as educating prescribers, counselling patients and simplifying dosing regimens, result in improved efficacy 29 .…”
Section: Discussionmentioning
confidence: 99%